Issues affecting the use of information and communication technology among the elderly: a case study on jenii - Mohd Yusof Abdullah; Ali Salman; Norizan Abdul Razak; Noor Fariza Mohd Noor; Jalaluddin Abdul Malek (Universiti Kebangsaan Malaysian, 2012)
The diffusion of information and communication technology (ICT) for adoption among the elderly faces the issue of reluctant to adopt and use the technology. Unlike some of the other categories of users, individuals in this category show little interest to use ICT. Reasons for not using ICT among the elderly are fear of the technology, do not know how to use, do not need the computer, and cannot afford to buy computer and fee for Internet connection. As the elderly are perceived to be low ICT literate and fear to technology, their desire to use the technology need to be develop through provision of simple and easy to use technology. A simple gadget called Jendela Informasi Anda (literally translate as your window of information) or in short JENii was developed and introduced to this segment of the population as a strategic step to bridge the age digital divide. JENii contains easy applications and steps to teach the elderly on how to operate the gadget, how to access the content and how to overcome minor technical problems. This paper reports on the findings from the impact study on the use of JENii among the 26 pioneer users in Kota Kinabalu areas in East Malaysia. The focus of the discussion is on perception and experiences of users in using JENii. The study employed survey and focus group discussion. The findings indicate that the users’ interest to use JENii depend on the knowledge to operate JENii i.e. to on and off, use the icons, and seek the information. Some users report that they don’t use JENii often because they forget how to operate it and the content is not updated. Thus, the users feel frustrated and their motivation and interest level to use JENii will definitely decrease. The paper concludes that the introduction of JENii is a right step by the government to encourage wider usage of ICT and to address the issue of digital divide among the society, especially the marginalized group such as the adults and elderly.